Can 10% hydrofluoric acid be used for reconditioning of orthodontic brackets? - Daniela D Pompeo; Henrique D Rosário; Beatriz MV Lopes; Paulo F Cesar; Luiz Renato Paranhos (Wolters Kluwer Medknow Publications, 2016)
Context: Bracket debonding is a common problem during orthodontic treatment. This type of failure is associated to masticatory forces, poor adhesion, and the need for repositioning the piece. Aims: The objective of this work was to compare the shear bond strength of debonded brackets that were reconditioned using different protocols (alumina blasting versus hydrofluoric etching). Settings and Design: This was an in vitro experimental study with 45 stainless steel orthodontic brackets. Subjects and Methods: They were randomly divided into three groups: (1) New brackets (n = 15), (2) brackets reconditioned using 10% hydrofluoric acid for 60 s (n = 15), and (3) brackets reconditioned by aluminum oxide blasting until complete removal of the remaining resin (n = 15). In Groups 2 and 3, the insertion of composite resin proceeded in two stages to simulate a type of bracket failure in which the bonding resin was left at the bracket base. For the shear test, the assembly composed by the metallic support, and specimen was taken to the Instron universal testing machine in which the specimens were loaded using a semicircle-shaped active tip in the region of the bonding interface parallel to the surface of the bracket at a speed of 0.5 mm/min. Statistical Analysis Used: The data were subjected to D'Agostino's normality test to have their distribution checked. Analysis of variance and Tukey's test (P < 0.01) were used to compare the findings between groups. Results: The results indicated that Group 1 (new brackets) showed higher bond strength than that obtained for the group treated with hydrofluoric acid (Group 2, P < 0.01). The bond strength value obtained for the group treated with alumina blasting (Group 3) was statistically similar to those obtained for Groups 1 and 2. Conclusions: The aluminum oxide blasting technique was effective for the reconditioning of orthodontic brackets. Nevertheless, the reconditioning technique using 10% fluoridric acid for 60 s was not efficient for clinical use.